(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Spinal Epidural Lipomatosis (SEL) is a rare cause of Lumbar pain and Spinal canal stenosis due to an excessive amount of epidural fat in the Spinal canal. Conservative treatments generally aimed to decrease the thickness of adipose tissue in the epidural space, but the majority of patients tend to undergo surgical decompression to relieve neurological symptoms. The present study was aimed at treating a 23-year-old male patient admitted to the Government Ayurveda college, Thiruvananthapuram, who was diagnosed as Lumbar spinal canal stenosis due to Spinal Epidural Lipomatosis through MRI screening. While considering the etiopathogenesis of this disease, it cannot be correlated to a specific Vyadhi as per Ayurvedic classics. However, a line of treatment can be adopted by considering the Vyadhi ghatakas, such as Srotovaigunya, Avarana Vata, as well as diseases like Gridrasi and Pakwashaya gata vata. Pachana, Deepana, Snehana, Swedana, and Sodhana were the treatment protocols adopted in this case. Here, these treatment protocols were found effective in treating Spinal epidural lipomatosis. Along with a review MRI screening, Modified Oswestry LBP Disability index (ODI), Swiss Spinal Stenosis scoring (SSS), and Visual Analogue Scale (VAS) were also used for assessment. Before treatment, ODI was 40% and reduced to 24% after treatment, and after a follow-up 2 months, it was reduced to 15%. SSS before treatment was 28 and reduced to 18 after treatment, and on follow-up reduced to 9. VAS score at the time admission was 10/10 and subsequently reduced to 4/10; on follow-up, it was 2/10.